SIMILAR ADSORPTION PARAMETERS FOR TRACE METALS WITH DIFFERENT AQUATIC PARTICLES - Müller B.; Duffek A. (My University, 2001)
Conditional surface binding constants and complexation capacities for Zn, Pb, Cd, and Cu were determined from surface titration experiments of heterogeneous natural aquatic particulate matter of different origin and composition. Metals and particles were evaluated in naturally occurring concentration ranges in river water.The adsorption of trace metals can be adequately described with a single conditional binding constant over a wide range of metal : particle ratios. Binding constants for aquatic particles at pH 8.0 are remarkably independent from particle composition and are specific for each metal: log Kads Zn = 8.39, log Kads Pb = 9.67, log Kads Cd = 8.61, log ads Cu = 9.84. From competition experiments with Ca and Pb we extracted a sorption coefficient for Ca of log Kads Ca = 2.5 (pH 8.0). Maximum surface binding capacities for all metal ions were found for particles containing high fractions of Mn-oxides which are associated with large specific surface areas. Generally, we found sorption capacities to decrease in the sequence Cu Pb, Zn > Cd.The experiments suggest that the conditional surface binding constants and complexation capacities are applicable to model trace metal adsorption in the concentration ranges of natural waters under conditions similar to the experiments. Results also imply that the chemical nature of particle surface sites is rather uniform in the intermediate concentration range or that the array of binding sites averages out differences in sorption strength over the prevailing concentration range of metal ions, respectively.
Keywords: adsorption; trace metal; natural particles; surface ligands; surface binding constants; complexation capacity; competitive sorption